Talk to me! Possibilities of constructing children's voices in the domestic research context. (February 2017) - Noppari, Elina; Uusitalo, Niina; Kupiainen, Reijo
This self-reflective article explores the possibilities of producing children's 'voice' in the domestic research context. We look at producing voices as the process of giving an account of children's meaning making and life. We examine the methodological challenges of producing voices in the home environment from three perspectives: power, trust and ethics. The findings presented in the article are based on an ongoing longitudinal study of Finnish children's media environments, which began in 2007 and will continue through 2016.